2018
DOI: 10.1016/j.lungcan.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography in the evaluation of malignant pleural mesothelioma—Association of tumor size to a sarcomatoid histology, a more advanced TNM stage and poor survival

Abstract: In this study, we demonstrate a novel approach for MPM tumor size evaluation that has a strong relationship with mortality, sarcomatoid histology and TNM stage groups. TS could be used for prognostic purposes and it may be a useful method for assessing therapy responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…38,39 In our previous study, we showed that a novel TS evaluation had independent prognostic impact with excellent intraclass correlation. 20 In this study, we used the same approach to assess MPM and found that activin A correlated with TS but not with TNM stage at baseline.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…38,39 In our previous study, we showed that a novel TS evaluation had independent prognostic impact with excellent intraclass correlation. 20 In this study, we used the same approach to assess MPM and found that activin A correlated with TS but not with TNM stage at baseline.…”
Section: Discussionmentioning
confidence: 83%
“…The tumor size (TS) was approximated using our previously published method, where the maximal tumor thickness on axial images is multiplied by the tumor extent. 20 The radiologic response to chemotherapy was evaluated using change in TS.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…37 We confirmed our previous finding that tumor size approximation with tumor thickness and extension was a better prognostic factor than CT stage. 16 The optimal treatment regimen remains controversial in MPM since only the benefit from combination chemotherapy has been established in prospective controlled clinical trials. 38 Although we found that surgery and chemotherapy were associated with longer survival, the effects of these treatment modalities on survival could be confounded by patient-driven factors in a nonrandomized setting.…”
Section: Discussionmentioning
confidence: 99%
“…with special experience in occupational radiology, and the mesothelioma size was estimated using a method where the maximal tumor thickness on axial images is multiplied by the tumor extent grade. 16 Pleural plaques were searched from both sides separately and then reported overall as being present or absent. The maximal thickness of pleural effusion was measured on axial planes.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…In accordance with our results, in their analysis the estimation of T was a better prognostic factor than TNM stage and was related to the sarcomatoid histology and TNM stages; moreover, the prognostic role of tumor extension was higher than that of tumor thickness. 26 Regarding the comparison with stage, we found that the combinations of TV groups and NPS groups had higher HRs than stage. These results are in line with other studies.…”
Section: Discussionmentioning
confidence: 82%